O εορτασμός της εθνικής επετείου στα Ιόνια Νησιά την περίοδο του Ιονίου Κράτους (1850-1864) - Δημητρίου, Γιάννα (Peri Istorias, 2022)
The national anniversary celebration is linked to ritual practices, which bear important symbolism aimed at retaining in the collective memory the formation of the nation and the heroic moments of the national narrative. After the Greek Revolution and the formation of the independent Greek state, it was essential to establish the celebration, marking the beginning of the revolution, as an event that opened a new era. It appears that the Ionians began to celebrate the national anniversary with strong symbolic – both political and national – content. There is already some information about the celebrations in Cephalonia, which relate these events to the emergence and strengthening of radicalism (a political movement against the British Protection). Relevant research in the press shows that the national day was celebrated in other islands, including Corfu, under the watchful eye of the British authorities. Social networks of the urban upper classes, which took the form of clubs, associations and societies with a more or less evident political character, were the first to organise these events. The text attempts to present how the Greek Revolution was commemorated in Corfu, and the perceived meaning of the celebration by the Corfiot people, through the newspaper articles during the period 1850–1863.